Short-term Memory Comparison between Stunted and Non-Stunted Groups - Sadikin, Irma Suwandi; Lubis, Leonardo; Djais, Julistio T. B. (Althea Medical Journal, 2018)
Background: Long-term insufficient nutritional needs will directly impact on the development and maturation of brain function. Disruption of development and maturation process in the brain is associated with decreased cognitive abilities. Frequently, the effect of long-term nutritional insufficiency has also height deficits called stunting.This study aimed to compare the short-term memory between stunted and non-stunted groups.Methods: A comparative study was conducted on 30 children in a non stunted group and 30 children in a stunted group. Children in both groups were selected from one of the elementary schools in Jatinangor using the simple random sampling method toward 3–5 for grade and 8–10 for age groups. The measurement of memory aspects for short-term memory used the Digit Span Test (forward and backward) and Simbol Modality Test. Results: The collected data were in normal and not normal distribution because the statistical test  used the independent-t test and Mann-Whitney. The mean memory score comparison between group 1 and group 2 on Digit Span Test Forward was 5.33:5.33 (p=0.994), Digit Span test Backward was 2.73:2.60 (p=0.440), and Symbol Modality Test was 20.90:19.60 (p=0.347).Conclusions: There is no significant difference in short-term memory between stunted and non–stunted groups, due to some confounding factors such as, environmental aspect, parent’s education level, socioeconomic, and genetic factors.